The effect of the coping strategy on the achievement of Arabic grammar among fifth-grade primary school students (Journal of the College of Basic Education, 2025)
The current research aims to identify (the effect of the confrontation strategy on the acquisition of Arabic grammar among students in the fifth grade of primary school). The researcher adopted the experimental method with partial control for the two research groups (experimental and control) As a research design, the researcher randomly selected the research sample consisting of (63) students, with (32) students in the experimental group, and (31) students in the control group. The researcher rewarded the two groups on variables (chronological age, Previous achievement, parents’ academic achievement) The researcher prepared an achievement test consisting of (30) test items from objective items. The results showed superiority among the students who studied Arabic grammar according to the coping strategy. For students who studied the same subject in the usual traditional way.